بدائع الصنائع میں شفعہ کے اسباب اور تملیک قبل القبض: فروعی اصول و اطلاق کا تحقیقی مطالعہ، کلاسیکی فقہ سے معاصر تناظر تک: Causes of Pre-emption and Transfer before Possession in Bada'i al-Sana'i: A Research Study of Branch Principles and Applications from Classical Fiqh to Contemporary (Al-Aasar, 2025)
Shuf‘ah (pre-emption) is an important right in Islamic property law, granted to a co-owner or an adjoining neighbor when a shared or adjacent property is sold to a third party. The primary objective of this right is to prevent the entry of unfamiliar or unsuitable buyers and to preserve social harmony around the property. The causes of the obligation of Shuf‘ah include the valid conclusion of sale, the existence of a specific property, and the fulfillment of certain essential conditions through which this right becomes confirmed. In classical juristic discourse, significant importance is attached to determining the exact stage at which the right of Shuf‘ah is established and the conditions necessary for its legitimate claim.The issue of al-tamlik qabla al-qabd (transfer of ownership before possession) is a particularly important and intricate topic in this regard. It refers to the situation in which ownership is legally and Islamically transferred after the sale but before the buyer takes possession. On this matter, the four major Sunni schools of law (madhāhib) and other jurists hold differing opinions. The Ḥanafī school, in certain circumstances, recognizes the right of Shuf‘ah even before possession, whereas the Shāfiʿī, Mālikī, and Ḥanbalī schools adopt different positions. These differences stem from variations in the interpretation of scriptural sources, the application of juristic maxims, and the conditions required for the establishment of ownership.This article presents a detailed legal analysis of the causes of the obligation of Shuf‘ah and the issue of al-tamlik qabla al-qabd, incorporating Qur’ānic and Sunnah evidence, classical juristic discussions, and a comparative study of the opinions of the four schools of law. It also examines the implementation of Shuf‘ah in modern legal systems and the effects of ownership transfer before possession. The research concludes that although the principles formulated in classical Islamic law remain strong in their legal and ethical foundations, modern legal frameworks, registration procedures, and judicial practices pose several challenges to their practical enforcement. In light of this, further ijtihād and scholarly efforts are needed to harmonize classical juristic principles with contemporary legal requirements.